2019
DOI: 10.1149/2.0272001jes
|View full text |Cite
|
Sign up to set email alerts
|

How to Design Lithium Ion Capacitors: Modelling, Mass Ratio of Electrodes and Pre-lithiation

Abstract: Lithium ion capacitors (LICs) store energy using double layer capacitance at the positive electrode and intercalation at the negative electrode. LICs offer the optimum power and energy density with longer cycle life for applications requiring short pulses of high power. However, the effect of electrode balancing and pre-lithiation on usable energy is rarely studied. In this work, a set of guidelines for optimum design of LICs with activated carbon (AC) as positive electrode and lithium titanium oxide (LTO) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…In addition, the mass ratio between the anode (battery type) and the cathode (capacitor type) plays an important role to increase the energy and power density, as well as the cycling life of the MICs. 29,48 The mass ratio between the two electrodes can be calculated according to the charge balance equation: 54 where m , C , and Δ E are the mass of the active materials, specific capacitance, and working voltage, respectively. Nevertheless, many studies have reported that an optimal electrochemical performance can be obtained when the negative charge is in excess.…”
Section: Construction and Operating Mechanisms Of Micsmentioning
confidence: 99%
“…In addition, the mass ratio between the anode (battery type) and the cathode (capacitor type) plays an important role to increase the energy and power density, as well as the cycling life of the MICs. 29,48 The mass ratio between the two electrodes can be calculated according to the charge balance equation: 54 where m , C , and Δ E are the mass of the active materials, specific capacitance, and working voltage, respectively. Nevertheless, many studies have reported that an optimal electrochemical performance can be obtained when the negative charge is in excess.…”
Section: Construction and Operating Mechanisms Of Micsmentioning
confidence: 99%
“…In comparison with dual‐ion batteries (DIBs) that comprise graphite as both anode and cathode, this hybrid configuration has an important difference such that the average concentration of charge carriers in the electrolyte changes during the charge–discharge process due to both‐in/both‐out mechanism in comparison with one‐in‐one‐out mechanism of DIBs. [ 14,15 ] Ideally, the cation intercalation will take place at a lower potential, whereas the anion insertion occurs at higher potentials. In the case of liquid electrolyte, the potential window is defined based on its lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO).…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of maximizing the output capacity, mass balance of the electrodes was performed [39–41] . In this regard, the charge stored in both electrodes must be equal Q+ =Q- and it is influenced by the specific capacitance of each electrode (C+,C- ), the active mass of the electrode materials (m+,m- ) and the working potential window (ΔE+,ΔE- ) [Eqs.…”
Section: Resultsmentioning
confidence: 99%